2010
DOI: 10.1142/s0218196710006035
|View full text |Cite
|
Sign up to set email alerts
|

Normal Forms for Automorphisms of Universal Coxeter Groups and Palindromic Automorphisms of Free Groups

Abstract: We explicitly construct Markov languages of normal forms for the groups in the title of the paper and closely related groups. A Markov language of normal forms is a choice of "preferred spelling" for each group element such that the collection of choices is particularly simple in a language theoretic sense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Using geometric techniques, Glover and Jensen [5] proved this conjecture and also calculated the virtual cohomological dimension of ΠA n . Using methods from logic theory, Piggott and Ruane [12] constructed Markov languages of normal forms for ΠA n . The pure palindromic automorphism group is defined as P ΠA n = µ ij , t k | 1 ≤ i = j ≤ n and 1 ≤ k ≤ n .…”
Section: The Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Using geometric techniques, Glover and Jensen [5] proved this conjecture and also calculated the virtual cohomological dimension of ΠA n . Using methods from logic theory, Piggott and Ruane [12] constructed Markov languages of normal forms for ΠA n . The pure palindromic automorphism group is defined as P ΠA n = µ ij , t k | 1 ≤ i = j ≤ n and 1 ≤ k ≤ n .…”
Section: The Groupmentioning
confidence: 99%
“…Clearly, IA n ∩ EΠA ′ n ⊂ IA n ∩ ΠA n = P I n . In [3], Fullarton showed that P I n is normally generated in ΠA n by the automorphisms [µ 12 3 and hence they also lie in IA n ∩EΠA ′ n . Note that, IA n is a normal subgroup of Aut(F n ).…”
mentioning
confidence: 99%
“…Extending this work in [13], Jensen, McCommand and Meier computed the Euler characteristic of ΠA(F n ) and EΠA(F n ). In [16], Piggott and Ruane constructed Markov languages of normal forms for ΠA(F n ) using methods from logic theory. In [18,19], Nekritsukhin investigated some basic group theoretic questions about ΠA(F n ).…”
Section: Introductionmentioning
confidence: 99%